PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA FISIKA BERBASIS MODEL BRAIN-BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS VII SMP - Silvia Junika Andayana Saragih; Zulhelmi Zulhelmi; M. Rahmad M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The objective of this research was to develop a valid learning devices based on a model brain based learning on the matterial the temperature and changes in class VII SMP. This type of research is Research and Development (R&D). The data collection instruments used are the learning devices validation sheets. The learning devices validation sheets is given to 3 validators who are experts in the field for assessments on the learning devices validation sheets. The data analysis technique uses a quantitative descriptive analysis based on aspects on each learning device. Research indicates that the learning tools developed of RPP, LKPD, and cognitive learning test instruments were valid with an average validation value of 3.41 in the high category. Based on data analysis it can be concluded that the BBL model of learning tools is suitable for use in class VII Junior High School.Key Words: Learning Devices, Brain-Based Learning, Temperature and Change, Cognitive Learning Results